Środki społecznego przekazu w pontyfikacie Jana Pawła II - Narożna, Dominika (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
Mass media are the field of research interest of Pope John Paul II (the years of pontificate 1978–2005). The Bishop of Rome doesn’t deny the existence of them. He notices both the positive and dangers coming from their functioning. A lot of media institutions from the press to the Internet websites work for his good use. The author of the academic article emphasizes that the Pope – the Pole makes good use of the media for popularization of the Roman Catholic Church thought. Being a great authority with unique personality the Pope enjoys popularity from the media which are not responsible to him. The media present both his virtues such as: oratorical art., the ability to use symbolism, and weaknesses like his physical disability in the last years of his life. However, Karol Wojty³a’s reflections on the media should serve the creation of proper usage of theses tools in order to realize the common good.